study the repair of the various difficult forms of hypospadias using one-stage Island – flap Technic (Modification of Hodgsin and Device method). - Kanan, Mohammad; Ali, Wageh; Zbehe, Maged (Latakia University Journal -Medical Sciences Series, 2018)
This research is important because hypospadias is very common, there are many surgical methods to repair this defect , and there are many difficult forms of this deformity requiring a selected technique for the repair. This prospective study was conducted on 30 patients diagnosed to have difficult forms of hypospadias (penile , scrotal , chordee , proximal , and hypospadias with shortening of urethra) at Al-Assad University Hospital , Lattakia , Syria , during the period between October 2014 – October 2016. The surgical technique (Hodgsin and Device) was performed with some modification. It was done without neither cystostomy nor compression ligament as described in the original technique and a permanent urinary catheter was inserted with normal dressing instead of cystostomy . Camera imaging for each patient was done before and after surgery . Patients were followed-up for 6 months, and complications were documented . A total of 30 children with mean age of 3.6 years presented for hypospadias repair . Indications for surgical repair were penile or scrotal hypospadias (18 patients) (60%) , unsuccessful previous surgery (8 patients) (26.7%) , and shortening of urethra (4 patients) (13.3%) . Complications occurred in 7 patients (23.3%) . The most common complications were fistulas (3 patients – 10%) , meatal stenosis (1 patient – 3.3% ) , stricture (1 patient – 3.3%) , diverticulum (1 patient – 3.3%) , and dehiscence (1 patient -3.3%) . The outcomes of our study were good compared with the results of other studies on different surgical techniques worldwide , with almost a similar complication rate , despite the lack of resources in our country. دراسة إصلاح مختلف الأشكال الصعبة للمبال التحتاني بتقنية شريحة جلدية موعّاة بمرحلة واحدة (Island-Flap Technic) (Hodgsin and Deviceتعديل لطريقة ( تنبع أهمية البحث من شيوع هذا التشوه وكثرة الطرق الجراحية لإصلاح المبال التحتاني و وجود بعض الاشكال الصعبة من المبال التحتاني تحتاج لتقنية منتقاة من أجل هذا الإصلاح. أُجريت هذه الدراسة المستقبلية على 30 مريض مع تشخيص مبال تحتاني في مشفى الأسد الجامعي , اللاذقية, سوريا , في الفترة الممتدة ما بين شهري تشرين أول 2014 و نشرين أول 2016 . تم اختيار الاطفال الذين لديهم مبال تحتاني من الاشكال الصعبة و التي تشمل المبال التحتاني القضيبي أو الصفني , المبال التحتاني مع انحناء القضيب , و قصرالاحليل . كما تم اختيار بعض الأطفال الذين لديهم المبال التحتاني قريب(قضيبي أو صفني) بدون أذية للقلفة . تم إجراء التقنية الجراحية (Hodgsin and Device) مع بعض التعديل و هو عدم وضع فغر مثانة و لا رباط ضاغط حسب ما هو موصوف بالتقنية الأصلية و وضع قثطرة بولية دائمة بدلاً عن الفغر مع ضماد عادي . قمنا بإجراء تصويربالكاميرا و توثيق لكل مريض قبل و بعد العمل الجراحي و متابعة المرضى لمدة 6 اشهر و توثيق حدوث المضاعفات . حيث بلغ متوسط أعمار المرضى 3.6 سنة , شكل المبال التحتاني ذو التوضع القضيبي أو الصفني غالبية استطبابات التداخل الجراحي في دراستنا بواقع 18 مريض (60% من مرضى العينة) , في حين شكل التداخل الجراحي السابق غير الناجح 26.7% بواقع 8 مرضى , و قصر الإحليل 13.3% بواقع 4 مرضى . كان معدل حدوث المضاعفات في دراستنا 23.3% (7 مرضى) , أشيع المضاعفات التي حدثت هي النواسير (3 مرضى – 10%) , تضيق في صماخ الإحليل مريض واحد (3.3%) , تضيق في منطقة الوصل مريض واحد (3.3%) , رتج إحليلي مريض واحد (3.3%) , و تفزر الجرح مريض واحد (3.3%) . و كانت نتائج دراستنا حول إصلاح مختلف الأشكال الصعبة للمبال التحتاني بتقنية شريحة جلدية موعاة بمرحلة واحدة (تعديل لطريقة Hodgsin and Device) , جيدةً بالمقارنة مع نتائج الإصلاح الجراحي للمبال التحتاني عالمياً بمختلف التقنيات و ذات معدل مضاعفات مماثل لها تقريباً , و ذلك على الرغم من قلة الإمكانيات لدينا .